Pengembangan Variasi Latihan Smash Bola Voli Berupa Video Tutorial Pada Ekstrakurikuler MA Maarif Sukorejo - Anggraeni, Galuh Kemala; Pratama, Indra Gunawan (CV. ITTC INDONESIA, 2024)
game rules. Nowadays, volleyball is not only played for health and fitness purposes, but has developed into a sports industry that demands achievement. High school students are quite interested in playing volleyball, because volleyball is easy to play anywhere. This type of research uses a development method using the Bord and Gall (2007) model which consists of 7 stages, namely, data collection, product design, expert validation testing, initial product revision, small scale product trials, large scale product trials, product results. Based on the digital media expert's validation test, a percentage result of 96% was obtained with a very valid category. Before carrying out small-scale trials, the researchers validated it with volleyball game experts and obtained a percentage of 92.8% with a valid category for use without revision. And validation with volleyball coaching experts obtained a percentage result of 86.4% with the valid category used with minor revisions. Small scale product trials were carried out by distributing questionnaires taking 12 volleyball extracurricular athletes. The small scale trials yielded a percentage of 78.9% with a valid category for use with minor revisions to variations in target code smash training. Large-scale trials were carried out by distributing questionnaires taking 25 volleyball extracurricular athletes. Large-scale trials obtained a percentage of 86.64% with a valid category for use without revision.